1996
DOI: 10.1093/mnras/279.2.673
|View full text |Cite
|
Sign up to set email alerts
|

Three-integral oblate galaxy models

Abstract: A simple numerical scheme is presented for the construction of three-integral phasespace distribution functions for oblate galaxy models with a gravitational potential of St ackel form, and an arbitrary axisymmetric luminous density distribution. The intrinsic velocity moments can be obtained simultaneously with little extra e ort. The distribution of the inner and outer turning points of the short-axis tube orbits that are populated can be speci ed freely, and is chosen in advance. The entire distribution fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Sellwood & Valluri found stability to axisymmetric modes at an axis ratio of ∼ 1 : 4 in their models. Ringlike modes in axisymmetric models were also reported by and Robijn (1995).…”
Section: Instabilities In Radially-cold Modelssupporting
confidence: 57%
See 1 more Smart Citation
“…Sellwood & Valluri found stability to axisymmetric modes at an axis ratio of ∼ 1 : 4 in their models. Ringlike modes in axisymmetric models were also reported by and Robijn (1995).…”
Section: Instabilities In Radially-cold Modelssupporting
confidence: 57%
“…Sellwood & Valluri found that the lopsided modes became less important as the net rotation of their models was increased, but they persisted even in models with net angular momentum 90% that of a maximally rotating model. Robijn (1995) carried out a normal-mode analysis of Kuz'min-Kutuzov models with little radial pressure and confirmed the Merritt & Stiavelli result that such models were unstable to lopsided modes regardless of axis ratio. He found that the growth rate of lopsided modes was more strongly affected by increasing the radial velocity dispersion than by adding net rotation.…”
Section: Instabilities In Radially-cold Modelssupporting
confidence: 54%
“…It was long believed that elliptical galaxy is oblate due to the flattening about the axis of rotation. Theoretical supports for oblate galaxy could be found in Dehnen & Gerhard (1994); Robijn & de Zeeuw (1996) and also references therein. An objection was then made based on the observed rotational velocity of galaxies that led to another propositions for prolate galaxy (e.g.…”
Section: Introductionmentioning
confidence: 84%
“…Two more follow from the fact that T φφ is perpendicular to the (complete) z ‐axis, and thus coincides with T λλ and T νν on the part between and beyond the foci, respectively: For oblate models with thin S‐tube orbits ( T λλ ≡ 0, see ), the analytical solution of was derived by Bishop (1987) and by de Zeeuw & Hunter (1990). Robijn & de Zeeuw (1996) obtained the second‐order velocity moments for models in which the thin‐tube orbits were thickened iteratively. Dejonghe & de Zeeuw (1988, Appendix D) found a general solution by integrating along characteristics.…”
Section: The Jeans Equations For Separable Modelsmentioning
confidence: 99%
“…For oblate models with thin S-tube orbits (T λλ ≡ 0, see §2.5.6), the analytical solution of (2.22) was derived by Bishop (1987) and by de Zeeuw & . Robijn & de Zeeuw (1996) obtained the second-order velocity moments for models in which the thin tube orbits were thickened iteratively. Dejonghe & de Zeeuw (1988, Appendix D) found a general solution by integrating along characteristics.…”
Section: Prolate Spheroidal Coordinates: Oblate Potentialsmentioning
confidence: 99%